Causes of Microcracks Silicon Coated in the inside Pipes - Ibrahimova, E.N. (Herald of Azerbaijan Engineering Academy, 2023)
Disappointments are seen in pipelines of oil field and oil refining gear working in high temperature, pressure and synthetically dynamic climate after a brief time of activity. Research and testing have shown that silicon-coated pipes’ service lives are greatly reduced by defects, including roughness on the inner surface of the pipe, microscopic bubbles, and macro- and microcrack layers. The paper that is being discussed looks at the root causes of these flaws and offers solutions. The research was carried out in "Khazar Pipe Coatings" and "Socar” companies. The quality coating within the pipe and their diagnostic techniques are described in the text.